S23 Effectiveness of a risk-stratified clinical & imaging surveillance protocol (LNC-PATH) following surgical resection of lung cancer. (11th November 2022) - Brockelsby, C; Bradley, P; Craig, C; Ryan, D; Martin, J; Lyons, J; Sinnott, N; Crosbie, P; Booton, R; Balata, H; Evison, M
Abstract : Introduction: Greater Manchester (GM) has implemented a standardised, risk-stratified follow-up protocol after surgical resection of lung cancer (LNC-PATH protocol) which de-intensifies surveillance in low-risk patients and intensifies surveillance in high-risk patients. 1 This evaluation assessed the clinical effectiveness of this protocol. Methods: A prospective analysis of the LNC-PATH protocol at a single centre physician-led survivorship service. Clinical effectiveness was assessed by the overall proportion of disease recurrences, proportion of disease recurrences detected through the standardised protocol, the pattern of disease recurrence and the subsequent treatment delivered stratified by risk category in the period between 01/01/2016 and 31/12/2019. We also analysed the site of disease recurrence identified outside the protocol. Results: 250 patients under risk stratified surveillance in the study period; 70% (176/250) of patients were low-risk, 22% (54/250) moderate-risk and 8% (20/250) high-risk ( table 1 ). Overall, 15% (38/250) of patients were diagnosed with disease recurrence within the first two years of surgical resection; 8% (14/176) in the low-risk, 24% (13/54) in the moderate-risk and 55% in the high-risk group (11/20). The LNC-PATH protocol identified 71% (27/38) of disease recurrences through routine surveillance; 57% (8/14) in the low-risk, 69% (9/13) in the moderate-risk and 91% (10/11) in the high-risk groups. 56% (15/27) of patients with disease recurrence detected via LNC-PATH had isolated local or thoracic lymph node recurrence. A total of 56% (15/27) patients underwent curative-intent treatment of disease recurrence and 78% (21/27) of patients underwent any treatment for anti-cancer therapy. In the 11 patients (6/11, 4/11 and 1/11 in low, moderate and high-risk groups respectively) that presented with symptomatic disease recurrence outside of the LNC-PATH protocol, 55% (6/11) were intra-cranial recurrence and 45% (5/11) were visible on a CT chest and upper abdomen. Discussion: The LNC-PATH protocol appears to accurately stratify patients into different categories of risk for disease recurrence allowing an appropriate de-intensification or intensification of surveillance and maximising the efficiency of healthcare utilisation. The protocol also appears to identify a high proportion of disease recurrence prior to symptomatic onset and facilitates access to anti-cancer treatment including curative-intent treatment. Reference: https://gmcancer.org.uk/wp-content/uploads/2021/10/greater-manchester-risk-stratified-follow-up-after-lung-cancer-surgery-p....pdf